Motivation of sports achievement and its relationship to some elements of fitness related to health in wheelchair basketball players - Sahnoune, Abdelatif; Kaddour Bendahma, Tarik (sports creativity, 2025)
Where the study aimed to know the relationship between the drivers of sports achievement in wheelchair basketball players. This researcher used the descriptive method to suit the nature of the study. The study sample included 17 individual (males and females) in the amateur club hodna disabled sports. Where the sample was chosen by intentional method (comprehensive inventory) as the researcher used each of the motivation measure of mathematical achievement designed by researcher Joe Wells 1982 and Arabized by Mohammed Hassan Allawi. Winnick and Short tests were also used to measure the level of fitness related to health. The most important results were: -There is a significant positive correlation between the motivation of athletic achievement and muscular strength among wheelchair basketball players. -There is a significant positive correlation between the motivation of athletic achievement and the periodic respiratory endurance of wheelchair basketball players - There is a significant correlation of moral significance statistically positive between the motivation of athletic achievement and some elements of fitness related to health among players on the wheelchair basketball